TOWARDS A PRISTINE ISLAMIC FINANCE: PRECONDITION - Oluwaseun Sulaiman Saidu (Share: Jurnal Ekonomi dan Keuangan Islam, 2020)
The need for an alternative to the current mainstream financial architecture is not in doubt. As exigent as this call might be through the Islamic finance conduit, it has to be done properly. This is particularly important if we must avoid associated shari’ah risks, avoid rubbing the face of the religion, Islam in the mud, and of course, if we must reap the benefits that accrue from following Allah’s dictates in all our affairs including “econo-financial” matters. This study aims at marshaling a path towards scripting a pristine and practicable Islamic finance by identifying two salient preconditions for it. It utilizes a diachronic approach whilst resorting to scriptural reasoning, historical evidence and were analyzed using inductive rationale. The study finds some unique issues cum scenarios that cannot be shoved or brushed aside as far as Islamic financing is concerned. viz; Scenario one: The impracticability of Islamic financing without an enabling Islamic Law; Scenario two: The non-implementability of Islamic financing without the Islamic man; Scenario three: Islamic finance orchestrated without an Islamic law but with an Islamic man; Scenario four: A “globalized” Islamic finance that can at best fit into a practicable legal micro-framework in today’s world; and Scenario five: A non-global Islamic finance within a practicable legal micro-framework.========================================================================================================Prasyarat Menuju Praktik Keuangan Islam Sejati. Kebutuhan akan sebuah arsitektur keuangan alternatif dari yang ada sekarang merupakan suatu hal yang tidak diragukan lagi. Walaupun seruan ini mungkin mendesak melalui saluran keuangan Islam, itu harus dilakukan dengan benar. Hal ini sangat penting untuk menghindari risiko yang terkait kesyariahan sistem keuangan dalam Islam, ibaratnya ini merupakan upaya untuk menghindari menggosok wajah agama Islam dengan lumpur. Jika kita harus menuai manfaat dari melaksanakan perintah Allah, maka itu ada dalam semua urusan termasuk masalah "Econo-financial". Kajian ini bertujuan menyusun jalan menuju skrip keuangan Islam yang murni dan praktis dengan mengidentifikasi dua prasyarat penting untuk itu. Studi ini menggunakan pendekatan diakronis dengan melakukan penalaran terhadap teks-teks keagamaan, bukti sejarah, dan dianalisis dengan rasionalisasi induktif. Penelitian ini menemukan beberapa masalah unik sekaligus skenario yang tidak dapat disingkirkan atau disingkirkan sejauh menyangkut keuangan Islam. yaitu; Skenario satu: Ketidakpraktisan pembiayaan keuangan syariah tanpa adanya hukum Islam yang memungkinkan; Skenario dua: Ketidakimplementasian pembiayaan keuangan Islam tanpa Islamic man; Skenario tiga: Keuangan Islam diatur tanpa hukum Islam tetapi dengan Islam man; Skenario empat: Keuangan Islam yang "diglobalisasi" yang paling sesuai dengan kerangka mikro hukum yang dapat diterapkan di dunia saat ini; dan Skenario lima: Keuangan Islam non-global dalam kerangka mikro hukum yang praktis.